2010
DOI: 10.1097/scs.0b013e3181cf6119
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Correction of Hard- and Soft-Tissue Facial Asymmetry

Abstract: The purpose of this study was to evaluate outcomes of simultaneous correction of the hard- and soft-tissue facial asymmetry with face lift procedure using a resorbable fixation device (Endotine Ribbon; Coapt Systems, Palo Alto, CA) during bimaxillary orthognathic surgery in cases with severe facial asymmetry. The samples consisted of 8 patients (mean age, 23.3 [SD, 4.4] years; 8 skeletal class III and 2 class II malocclusion) who received bimaxillary orthognathic surgery and a face lift procedure using a resor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“… 3 However, asymmetry may persist when occlusal plane or lip canting persists. 4 In many cases of dentofacial deformities requiring orthognathic surgery, the inclination of the lip can be confirmed. Persistence of the lip canting after surgery results in reduced patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“… 3 However, asymmetry may persist when occlusal plane or lip canting persists. 4 In many cases of dentofacial deformities requiring orthognathic surgery, the inclination of the lip can be confirmed. Persistence of the lip canting after surgery results in reduced patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, combination of various techniques such as bone contouring and fat graft injection prevailed and led to aesthetic results. Choi et al [ 6 ] reported bimaxillary orthognathic surgery combined with a face lift procedure plus the use of a resorbable fixation device. In this case, we judged that the patient did not require more facial bone surgery, yet face lift or fat graft injection did not seem sufficient to correct the asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…In our small group, except for patient 1 who received mandibular surgery alone, the correction rate six months after the operation was 48.9%. Choi et al [ 15 ] reported that correction rate of the lip cant was approximately 76.8% six months after simultaneous orthognathic surgery and the Endotine lift. In this study, the correction rate of the lip cant was 54.2% six months after the operation, and an average 74.2% three years after the operation.…”
Section: Discussionmentioning
confidence: 99%